Manajemen Konflik Budaya di Lingkungan Masyarakat Majemuk: Studi pada Tradisi dan Modernitas di Kota Padang - Gading Neylatun Nufus; Engeline Revila Vannessa; Vira Farisa Risman (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study examines cultural conflicts that emerge in the multicultural society of Padang City as a result of tensions between Minangkabau traditional values and the pressures of modern development. Using a qualitative approach with an interpretive paradigm and a case study design, data were collected through in-depth interviews, participant observation, and document analysis involving traditional leaders, cultural actors, youth communities, tourism practitioners, and government representatives. Findings reveal three dominant forms of conflict: (1) conflicts of meaning and sacredness arising from the transformation of Rumah Gadang into commercial spaces; (2) spatial and architectural identity conflicts triggered by urban modernization that neglects Minangkabau aesthetics; and (3) conflicts caused by the commodification of traditional performances for tourism. These conflicts occur due to different interpretations of cultural values and competing interests among actors. The study concludes that effective cultural conflict management requires a collaborative model integrating ABS-SBK values, adaptive governance, and the active role of young generations through digital cultural literacy. The proposed model offers strategic directions for sustaining Minangkabau culture while accommodating modern socio-economic demands..